1981
DOI: 10.1203/00006450-198109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Oral Human Immune Serum Globulin in the Gastrointestinal Tract of Low Birth Weight Infants

Abstract: Six immature infants were given oral feedings of 10% preservative-free human immune serum globulin ranging from 1 to 8 ml/kg/day. A seventh infant served as a control. Undigested and partially digested IgG was detected in the stools in significant quantities in all but the control infant. This coproantibody retained significant opsonic activity for type III group B streptococci as determined by a chemiluminescence assay, but lost most of its tetanus antibody activity. The newborn infants' enzymatic immaturity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 7 publications
3
32
0
Order By: Relevance
“…This outcome is confirmed by our in vivo studies, in which quantitative comparison of ingested and recovered activity of antibody to rotavirus allowed us to conclude that rvl00J0 of the antiviral activity survived gastrointestinal passage. Similar results were reported by other authors, who showed the survival of human serum immunoglobulins after being orally administered to low-birth-weight infants [38] and the conservation of specific antitoxic activity of bovine milk immunoglobulins in in vitro and in vivo digestion trials in rabbits [39]. Our results show that orally ad- We found appreciable amounts of neutralizing activity against human rotaviruses in the stools of concentrate C-treated infants.…”
Section: S a Plotkin Personal Communication)supporting
confidence: 91%
“…This outcome is confirmed by our in vivo studies, in which quantitative comparison of ingested and recovered activity of antibody to rotavirus allowed us to conclude that rvl00J0 of the antiviral activity survived gastrointestinal passage. Similar results were reported by other authors, who showed the survival of human serum immunoglobulins after being orally administered to low-birth-weight infants [38] and the conservation of specific antitoxic activity of bovine milk immunoglobulins in in vitro and in vivo digestion trials in rabbits [39]. Our results show that orally ad- We found appreciable amounts of neutralizing activity against human rotaviruses in the stools of concentrate C-treated infants.…”
Section: S a Plotkin Personal Communication)supporting
confidence: 91%
“…Orally administered Ig appears to be at least partially resistant to digestion in the GIT and intact active Ig has been -E-mail: p.j.moughan@massey.ac.nz reported in the stools of low birth weight infants given Ig orally (Blum et al, 1981). Roos et al (1995) demonstrated that as much as 19% of ingested IgG and IgM remain immunologically active in the intestine of adult humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, problems ofavailability, storage, and the possible transmission of infectious agents, such as cytomegalovirus, are factors that make widespread treatment or prophylaxis trials with human milk products difficult to accomplish. There have been several studies in man suggesting that passive immunity against infectious diarrheal agents may be achieved by the oral administration of immunoglobulin preparations derived from human or animal sera (12)(13)(14). To date, there have been no detailed studies of orally administered immunoglobulins in humans older than 13 wk ofage or in patients with chronic infectious diarrhea.…”
Section: Introductionmentioning
confidence: 99%